The cobra effect in TVET policy making : a macro-micro-macro-level analysis of exemplary cases from Germany - Schmees, Johannes Karl [Verfasser]; Grunau, Janika [Verfasser] (My University, 2025)
„Context: Unlike education policy for general education, technical and vocational education and training (TVET) policy often focuses on societal needs, ignoring the attitudes and subsequent behaviors of learners. As a result, the impact of TVET policies is not what was expected and sometimes even counterproductive. Starting from this, we use macro-micro-macro-level analysis inspired by Coleman's boat theorem to reflect on three exemplary cases of German TVET policy. These TVET policies have in common that they aim to reduce skills shortages in certain occupations. Approach: Our paper illustrates the value of macro-micro-macro-level analysis when looking at TVET policies and programs. To this end, we look at three exemplary cases. All the cases represent TVET policies and programs aimed at reducing skills shortages, a common issue for most countries in the world. One way of addressing those shortages are TVET policies of which we present here: (1) Increasing the permeability between TVET and higher education, (2) attracting workers for post-qualification and (3) directed career counselling for refugees. Using Coleman's boat theorem, we analyze the cases in terms of whether the policy strategies address the skills shortage adequately. We then compare the cases with each other to draw general conclusions regarding the connection of macro- and micro-level within policy making in TVET. Findings: A common finding among all three case studies is that the investigated policies and programs do not consider possible deviant considerations of actors at the micro-level adequately. Consequently, the actor's behaviors on the micro-level can contradict the intention of the policy. Conclusion: We conclude that it is essential to take micro-level perspectives into account when developing political strategies for TVET. Therefore, TVET policies and programs should be developed from a more subject-oriented perspective and as a second step include societal needs. Furthermore, TVET policies and programs have to be accomplished by reforms changing work conditions for the better. Only then, there is a chance for convergence of micro-level decisions and macro-level outcomes.“ (authors‘ abstract; BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; 370; Berufsbildungspolitik; Fachkräftemangel; Programmanalyse; Fallstudie